Hubungan Pengetahuan dan Kepatuhan Konsumsi Tablet Tambah Darah dengan Anemia Remaja Putri - Suffara, Inayati; Abdullah, Abdullah; Palupi, Rini; Muharramah, Alifiyanti (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Anemia is a condition in which the hemoglobin (Hb) level in the blood is lower than normal is caused by several factors, one of which is the level of knowledge and adherence to the consumption of iron supplements (TTD). The prevalence of anemia among female adolescents at MTs Al Huda Bandungbaru, Adiluwih Subdistrict, was 47%, and in 2024 it increased to 68.2%. This study aims to determine the relationship between the level of knowledge and the level of adherence to iron tablet consumption with the incidence of anemia in female adolescents at MTs Al Huda Bandungbaru, Adiluwih Subdistrict. Methods: This study is a quantitative study using a cross-sectional approach. The bivariate analysis in this study used the Gamma test. while the sample size was 80 students. Results: The results of this study show that 71.3% of female adolescents were anemic, with the majority having insufficient knowledge (45%) and a high level of non-compliance with iron supplement consumption (76.3%). The bivariate analysis showed a p-value < 0.05, indicating a significant relationship between the level of knowledge and adherence to iron supplement consumption with the incidence of anemia in female adolescents at MTs Al Huda Bandungbaru, Adiluwih Subdistrict. Conclusion: The high incidence of anemia in young women is influenced by a lack of knowledge and non-compliance with taking blood supplement tablets.